Preconcentration of Cadmium onto Amberlite XAD-4 Resin Loaded with 5-Br-PADAP and Determination by Anodic Stripping Differential Pulse Polarography - Ali Taher, Mohammad; Mostafavi, Ali; Rohani, Tahereh (Asian Journal of Chemistry, 2016)
A procedure for separation and preconcentration of trace amounts of cadmium has been proposed. For the retention of cadmium a column of Amberlite XAD-4 loaded with 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol (5-Br-PADAP) was used. Cadmium is quantitatively retained on the column at pH 9.5. The cadmium was removed from the column with 10.0 mL of 1 M nitric acid and determined by anodic stripping differential pulse polarography. A preconcentration factor of 100 was obtained. The detection limit value for the preconcentration of 1000 mL of aqueous solution of cadmium was 0.035 μg/mL. The precision for eight replicate determinations at the 1 μg/mL cadmium levels was 0.36% relative standard deviation (RSD), calculated with the peak height obtained. The calibration graph using the preconcentration system for cadmium was linear with a correlation coefficient of 0.9995 at levels near the detection limits up to at least 150 μg/mL. The method was successfully applied to the determination of cadmium in natural samples.